Osip Mandelstam in the French Anthologies of Russian Poetry (1925–1970) - Gamalova, Natalia (Literatūra, 2020)
The fates and fortunes of any national literature in a foreign culture is a multifaceted subject. And this is where the perception of Russian culture in France belongs. In France, the general public became aware of the life and works of Osip Mandelstam in the early seventies, when Nadezhda Mandelstam’s memoirs were published. Before 1970, only some translations of Mandelstam’s poems, the first one made by Chuzeville back in 1925, found their way to periodicals and anthologies. Information about the poet was spread to a great degree thanks to anthologies, as befits this genre of reading matter. During that period, the publishers of anthologies could either collaborate with translators (Slonim, Reavey), or translate the poetry themselves (Rais, Granoff). Journal articles and translations chime in and resonate with anthological publications.
Keywords: Mandelstam; anthology; poetry translation; anthology editor; periodicals